REBRANDING SIRUP KAYU MANIS ALFAFA MELALUI HIGHLIGHT VIDEO - DION ATMA WIJAYA, Dr. Syafwandi, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The goal of this research is to make a draft of cinnamon syrup promotion media in the form of Highlight Video which is used as the main media as well as supporting media that support the main media. The design of audio-visual media as a medium for rebranding alfafa cinnamon syrup through highlight videos is felt to explain about cinnamon syrup which is a typical souvenir of Kerinci so that it can be used as information material to increase knowledge for the Kerinci community on cinnamon syrup, so as to increase the amount connoisseurs of cinnamon syrup itself. The selection of Highlight Video tools is a great way to promote cinnamon syrup. How to deliver information through Highlight Video is expected to be responded well by many groups, ranging from the public to tourists. Through Highlight Video, it is hoped that it can be used as a tool to explain things about Kerinci cinnamon syrup. Rebranding alfafa cinnamon syrup through video highlights trying to convey all things related to cinnamon syrup, namely how to display the freshness contained in cinnamon syrup so that alfafa cinnamon syrup can be enjoyed by anyone, anytime and anywhere.The design of alfafa cinnamon syrup rebranding through video highlights was carried out through a research process in the form of collecting data by observing, interviewing and studying literature. The data is then used to develop stories and design concepts from visual communication principles such as cinematography, shooting angles, to be applied so that they can be easily understood in detail by the target audience.Keywords: Rebranding, Cinnamon Syrup, Highlight Video